Frequency Of Functional Outcome In Management Of Post Burn Neck Contractures - Memon, Sidra; Ali, Mansoor; Rsheed, Sadia; Bhatti, Aisha Masroor; Naz, Sameena (Journal of Rawalpindi Medical College, 2024)
Objective: To determine the frequency of functional outcomes in managing post-burn neck contractures. Descriptive study. At the department of plastic surgery. Methods: A total of 150 cases presenting from Liaquat University of Medical and Health Sciences with any degree of post-burn neck contracture admitted to the plastic surgery unit and fulfilling the inclusion criteria, were included in the study. A detailed clinical and radiological examination was carried out. Before the interventional procedure was instituted, the cause of burn injury and functional grade of neck contracture was documented. A follow-up of 6 months was done to evaluate the range of neck motion and postoperative improvement in neck extension to document patient satisfaction. All data was recorded on a predesigned proforma. Results: The average age of the patient was 29.67±7.67 years. Out of 150, 96 (64%) patients showed satisfactory outcomes, 52 (34.67%) had good outcomes and 2 (1.33%) patients were poor outcomes. Conclusion: After oral intubation and SSG resurfacing of the raw region, it can be stated that contracture release under tumescent anaesthesia is a successful treatment for individuals with post-burn contractures of the neck.